Effects of Seaweed Extracts on the Growth, Physiological Activity, Cane Yield and Sucrose Content of Sugarcane in China - Chen, Diwen; Zhou, Wenling; Yang, Jin; Ao, Junhua; Huang, Ying; Shen, Dachun; Jiang, Yong; Huang, Zhenrui; Shen, Hong (Frontiers in Plant Science, 2021)
Seaweed extracts (SEs) have been widely used as biostimulants in crop management due to their growth-promoting and stress-resistant effects. To date, there are few reports of the effect of SEs on sucrose content and cane yield. Here, we conducted a three-year field experiments (2017-2018-2019) in two areas (Suixi and Wengyuan) of China, to investigate the yield and sugar content of sugarcane in response to SE treatment at different growth stages. The results showed that spraying SEs once at seedling (S), early elongation (E), and early mature (M) stages respectively, once at S and E stages respectively, or once at the S stage increased the cane yield by 9.23, 9.01, and 3.33%, respectively, implying that SEs application at the early elongation stage played a vital role in promoting sugarcane growth. Photosynthetic parameters and nutrient efficiency analysis showed that spraying SEs at S and E stages enhanced the net photosynthetic rate, transpiration rate, and water use efficiency, and increased N, P, or K utilization efficiency, compared with those of the control. Notably, cane yield increasing rate of SEs in 2017 and 2018 were higher than those in 2019 in Wengyuan but lower than those in 2019 in Suixi. Interestingly, the total rainfall and monthly average rainfall in 2017 and 2018 were lower than those in 2019 in Wengyuan but higher than those in 2019 in Suixi. The results suggested that the yield increasing rate of SEs on sugarcane was better in less rainfall years. The sucrose content of sugarcane showed no difference between spraying SEs at the M stage alone or at the three growth stages but was higher than those of SE treatments at S and/or E stages. Enzyme activity analysis showed that spraying SEs at the M stage increased the activity of sucrose phosphate synthase activity by 9.14% in leaves and 15.16% in stems, and decreased soluble acid invertase activity in stems by 16.52%, which contributed to the sucrose increase of 5.00%.The above results suggested that SEs could increase cane yield and promote sucrose accumulation in sugarcane. The yield increasing effect was more obvious under conditions of drought stress.